+0  
 
0
190
2
avatar

$${\frac{{{log}}_{{\mathtt{2}}}{\left({\mathtt{4\,096}}\right)}}{{{log}}_{{\mathtt{x}}}{\left({\frac{{\mathtt{37}}}{{\mathtt{999}}}}\right)}}} = -{\mathtt{4}}$$

Guest Mar 14, 2015

Best Answer 

 #2
avatar
+5

$${\frac{{{log}}_{{\mathtt{2}}}{\left({\mathtt{4\,096}}\right)}}{{{log}}_{{\mathtt{x}}}{\left({\frac{{\mathtt{37}}}{{\mathtt{999}}}}\right)}}} = -{\mathtt{4}}$$

 

$${{log}}_{{\mathtt{2}}}{\left({\mathtt{4\,096}}\right)} = {\mathtt{12}}$$

 

$${\frac{{\mathtt{12}}}{{{log}}_{{\mathtt{x}}}{\left(\left({\frac{{\mathtt{37}}}{{\mathtt{999}}}}\right)\right)}}} = -{\mathtt{4}}$$

 

$${\mathtt{12}} = {\mathtt{\,-\,}}\left({\mathtt{4}}{\mathtt{\,\times\,}}{{log}}_{{\mathtt{x}}}{\left({\frac{{\mathtt{37}}}{{\mathtt{999}}}}\right)}\right)$$

 

$$-{\mathtt{3}} = {{log}}_{{\mathtt{x}}}{\left({\frac{{\mathtt{37}}}{{\mathtt{999}}}}\right)}$$

 

$${{\mathtt{x}}}^{-{\mathtt{3}}} = {\frac{{\mathtt{37}}}{{\mathtt{999}}}}$$

 

$${\frac{{\mathtt{1}}}{{{\mathtt{x}}}^{{\mathtt{3}}}}} = {\frac{{\mathtt{37}}}{{\mathtt{999}}}}$$

 

$${\mathtt{999}} = {\mathtt{37}}{\mathtt{\,\times\,}}{{\mathtt{x}}}^{{\mathtt{3}}}$$

 

$${\mathtt{27}} = {{\mathtt{x}}}^{{\mathtt{3}}}$$

 

$${\sqrt[{{\mathtt{{\mathtt{3}}}}}]{{\mathtt{27}}}} = {\mathtt{x}}$$

 

$${\mathtt{x}} = {\mathtt{3}}$$

Guest Mar 14, 2015
Sort: 

2+0 Answers

 #1
avatar+26399 
+5

 

See Anonymous's answer below.

Alan  Mar 14, 2015
 #2
avatar
+5
Best Answer

$${\frac{{{log}}_{{\mathtt{2}}}{\left({\mathtt{4\,096}}\right)}}{{{log}}_{{\mathtt{x}}}{\left({\frac{{\mathtt{37}}}{{\mathtt{999}}}}\right)}}} = -{\mathtt{4}}$$

 

$${{log}}_{{\mathtt{2}}}{\left({\mathtt{4\,096}}\right)} = {\mathtt{12}}$$

 

$${\frac{{\mathtt{12}}}{{{log}}_{{\mathtt{x}}}{\left(\left({\frac{{\mathtt{37}}}{{\mathtt{999}}}}\right)\right)}}} = -{\mathtt{4}}$$

 

$${\mathtt{12}} = {\mathtt{\,-\,}}\left({\mathtt{4}}{\mathtt{\,\times\,}}{{log}}_{{\mathtt{x}}}{\left({\frac{{\mathtt{37}}}{{\mathtt{999}}}}\right)}\right)$$

 

$$-{\mathtt{3}} = {{log}}_{{\mathtt{x}}}{\left({\frac{{\mathtt{37}}}{{\mathtt{999}}}}\right)}$$

 

$${{\mathtt{x}}}^{-{\mathtt{3}}} = {\frac{{\mathtt{37}}}{{\mathtt{999}}}}$$

 

$${\frac{{\mathtt{1}}}{{{\mathtt{x}}}^{{\mathtt{3}}}}} = {\frac{{\mathtt{37}}}{{\mathtt{999}}}}$$

 

$${\mathtt{999}} = {\mathtt{37}}{\mathtt{\,\times\,}}{{\mathtt{x}}}^{{\mathtt{3}}}$$

 

$${\mathtt{27}} = {{\mathtt{x}}}^{{\mathtt{3}}}$$

 

$${\sqrt[{{\mathtt{{\mathtt{3}}}}}]{{\mathtt{27}}}} = {\mathtt{x}}$$

 

$${\mathtt{x}} = {\mathtt{3}}$$

Guest Mar 14, 2015

6 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details